A Evolução das Parcerias Público-Privadas Hospitalares em Portugal - Ana Cristina Santos Cunha (2019)
Public-Private Partnerships (PPPs) are models that apply the private management principles to public facilities. There are three possible PPP's models: infrastructure, discrete clinical services and integrated. Portugal had an innovative approach in Europe and applied the integrated model since the beginning. In this kind of model, the private part of the partnership is responsible by hospital's construction and the clinical services management. Studies addressing PPPs quality were scarce and not conclusive until now, so we decided to analyze the PPPS productivity and economic indicators given by ACSS (Administração Central do Sistema de Saúde, IP). PPPs revealed good productivity outcomes, being the indicator with most improvement potential the average waiting time for surgery. Costs with operations and human resources showed good results, but we detected a necessity of improving the medicine's and clinical material's costs in the economical analysis.